Olfactometric and Chemical Characterisation of Gaseous Emission from Crude Oils - Elisa Polvara; Vittoria Legnani; Marzio Invernizzi; Selena Sironi (Molecules)
This study focuses on the olfactometric and chemical characterisation of gaseous and vapour emissions from different crude oils. To investigate this topic, laboratory experiments were set up to obtain comparable gaseous samples: they were estimated in terms of odour concentration (Cod), via dynamic olfactometry, and chemical-specific characterisation. It was found that, even if considered similar in regard to physical properties and chemical composition, the gaseous emissions of different crude oils are significantly different in terms of odorous potential. The observed discrepancy appears to be associated with the presence of volatile organic sulphur compounds (VOSCs), and the highest values of Cod were found in samples containing mercaptans and sulphides. In addition, from the conducted comparison, it appeared that crude odorous potential, in terms of Cod, is not strictly linked to the quantity of the volatile organic compounds (VOCs), H2S concentration, or a priori knowledge of the percentage of elemental sulphur in the crude; on the contrary, the presence of volatile organic sulphur compounds in the gaseous emissions is the most influential parameter for the odour potential of this matrix.